Heart failure in patients with human immunodeficiency virus infection: Epidemiology and management disparities. (1st September 2016) - Al-Kindi, Sadeer G.; ElAmm, Chantal; Ginwalla, Mahazarin; Mehanna, Emile; Zacharias, Michael; Benatti, Rodolfo; Oliveira, Guilherme H.; Longenecker, Chris T.
Abstract: Background: Persons living with HIV are at a higher risk of cardiovascular disease despite effective antiretroviral therapy and dramatic reductions in AIDS-related conditions. We sought to identify the epidemiology of heart failure (HF) among persons living with HIV in the United States in an era of contemporary antiretroviral therapy. Methods: Explorys is an electronic healthcare database that aggregates medical records from 23 healthcare systems nationwide. Using systemized nomenclature of medicine—clinical terms (SNOMED—CT), we identified adult patients (age > 18), who had active records over the past year (September 2014–September 2015). We described the prevalence of HF in HIV patients by demographics and treatment and compared them to HIV-uninfected controls. Results: Overall, there were 36, 400 patients with HIV and 12, 208, 430 controls. The overall prevalence of HF was 7.2% in HIV and 4.4% in controls (RR 1.66 [1.60–1.72], p < 0.0001). The relative risk of HF associated with HIV infection was higher among women and younger age groups. Patients receiving antiretroviral therapy had only marginally lower risk (6.4% vs. 7.7%, p < 0.0001) of HF compared to those who were untreated. Compared to uninfected patients with HF, HIV patients with HF were less likely to receive antiplatelet drugs, statins, diuretics, and ACE/ARBs (p < 0.0001 for all comparisons). For patients with HIV and HF, receiving care from a cardiologist was associated with higher use of antiplatelets, statins, betablockers, ACE/ARBs, and diuretics. Conclusions: Persons with HIV are at higher risk for HF in this large contemporary sample that includes both men and women. Although the prevalence of heart failure is higher in older HIV patients, the relative risk associated with HIV is highest in young people and in women. HIV patients are less likely to have HF optimally treated, but cardiology referral was associated with higher treatment rates.